2021
DOI: 10.1007/s12026-021-09183-7
|View full text |Cite
|
Sign up to set email alerts
|

Native and IgE-primed rat peritoneal mast cells exert pro-inflammatory activity and migrate in response to yeast zymosan upon Dectin-1 engagement

Abstract: Mast cells (MCs) play an essential role in host defense, primarily because of their location, their ability to pathogen destruction via several mechanisms, and the pattern recognition receptors they express. Even though most data is available regarding MC activation by various bacteria- or virus-derived molecules, those cells’ activity in response to constituents associated with fungi is not recognized enough. Our research aimed to address whether Saccharomyces cerevisiae-derived zymosan, i.e., β-(1,3)-glucan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…In turn, stimulation with zymosan results in an increase of IL-33 mRNA expression [88] as well as LTB 4 , LTC 4 , IL-1β, and GM-CSF synthesis by CBMCs [35,84]. Moreover, our paper reported that PMCs release cysLTs, IFNs, GM-CSF, TNF, and CCL2 in response to zymosan [83]. It has also been demonstrated that PbPga1 protein, a surface antigen of P. brasiliensis yeast, induces IL-6 release from RBL-2H3 cells [63].…”
Section: Effect Of Fungus-derived Molecules On Mcsmentioning
confidence: 56%
See 3 more Smart Citations
“…In turn, stimulation with zymosan results in an increase of IL-33 mRNA expression [88] as well as LTB 4 , LTC 4 , IL-1β, and GM-CSF synthesis by CBMCs [35,84]. Moreover, our paper reported that PMCs release cysLTs, IFNs, GM-CSF, TNF, and CCL2 in response to zymosan [83]. It has also been demonstrated that PbPga1 protein, a surface antigen of P. brasiliensis yeast, induces IL-6 release from RBL-2H3 cells [63].…”
Section: Effect Of Fungus-derived Molecules On Mcsmentioning
confidence: 56%
“…It has been established that zymosan from S. cerevisiae stimulated ROS and NO generation by murine BMMCs [34,78]. We have recently documented that zymosan and mannan, as well as curdlan, also promote ROS generation by rat PMCs [38,82,83]. Some fungus-associated molecules promote MC chemotactic activity.…”
Section: Effect Of Fungus-derived Molecules On Mcsmentioning
confidence: 96%
See 2 more Smart Citations
“…Dectin-1 can recognize β-glucans and trigger a variety of cellular responses such as phagocytosis and the production of cytokines. Zymosan, a β-glucan derived from yeast of Saccharomyces cerevisiae , for example, induced mature mice peritoneal MCs migration and pro-inflammatory expression via Dectin-1 ( 19 ). Similar results were observed in human cord blood-derived mast cells (CBMCs).…”
Section: Fungi Recognition Receptors On Mcsmentioning
confidence: 99%